2022
DOI: 10.1155/2022/5613046
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification, Optimization, and Application of Galactomannan-Based Edible Coating Formulations for Guava Using Response Surface Methodology

Abstract: Galactomannan from fenugreek and guar seeds were extracted, purified, and used in edible coatings, optimized via response surface methodology. The results showed that the emulsifying capacity and stability of fenugreek galactomannan (FG) and guar galactomannan (GG) increased with increase in the concentration of galactomannan up to 0.5–1%. The average optimized values of FG and GG in edible coatings were predicted to be 1.71% and 2.11% for weight loss, 0.72% and 2.14% for firmness, 1.02% and 1.44% for TSS, 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Lycopene is a carotenoid associated to color change during ripening [45,46]. Previous studies have shown that in ripening fruits chlorophyll degradation and lycopene accumulation are positively correlated [47]. Te present study shows that lycopene and β-carotene contents were lower in treated fruits compared to control fruits, indicating that the coating solutions formulated with cofee leaf extract, starch, and Gum Arabic slowed down the degradation of chlorophyll, and the synthesis of carotenoids as well.…”
Section: Efects Of Edible Coating On Lycopene and β-Carotenesupporting
confidence: 57%
“…Lycopene is a carotenoid associated to color change during ripening [45,46]. Previous studies have shown that in ripening fruits chlorophyll degradation and lycopene accumulation are positively correlated [47]. Te present study shows that lycopene and β-carotene contents were lower in treated fruits compared to control fruits, indicating that the coating solutions formulated with cofee leaf extract, starch, and Gum Arabic slowed down the degradation of chlorophyll, and the synthesis of carotenoids as well.…”
Section: Efects Of Edible Coating On Lycopene and β-Carotenesupporting
confidence: 57%
“…Response surface methodology (RSM) is a test design method proposed by Box et al It is an optimization method that integrates test design and mathematical modeling [22][23][24][25][26][27]. By performing tests on representative local points, the functional relationship between factors and results in the global scope is regressed and fitted, and the optimal level value of each element is obtained.…”
Section: Response Surface Methodology and Its Application In Dance He...mentioning
confidence: 99%
“…In recent years, the progress of computer and information technology [18][19][20][21][22][23] has also provided a powerful tool for the dance health and training safety analysis of this study. In order to promote the safety of dance teaching and competition, this study adopts response surface methodology [22] to study the accidental injuries and characteristics in dance teaching and competition, analyzes the causes, and puts forward corresponding safety precautions to reduce the incidence of injuries in safety measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharide-based coatings are the most used materials to extend the shelf life of fruits and vegetables. Examples of these materials include sodium alginate [ 16 ], chitosan [ 17 ], galactomannans [ 18 ], pullulan [ 19 , 20 ], pectin [ 21 ], among others.…”
Section: Introductionmentioning
confidence: 99%